Muḥammad and his followers in context: the religious map of late antique Arabia - Lindstedt, Ilkka (Islamic history and civilization, 2024)
"This book surveys and analyzes changes in religious groups and identities in late antique Arabia, ca. 300--700 CE. It engages with contemporary and material evidence: for example, inscriptions, archaeological remains, Arabic poetry, the Qur'an, and the so-called Constitution of Medina. Also, it suggests ways to deal with the later Arabic historiographical and other literary texts. The issue of social identities and their processes are central to the study. For instance, how did Arabian ethnic and religious identities intersect on the eve of Islam? The book suggests that the changes in social groups were more piecemeal than previously thought"--